Some questionings to the teaching of public international law in the peruvian context - Rosales Zamora, Pablo (2022)
The assumption that public international law has a homogeneous way of being  conceived is one of the major problems observed in its teaching in Peru. This article aims to  deconstruct this preconception based on two critics. The first criticism is against the ideological  universality that the debate between normativism and jusnaturalism assumes, with the consequent  revelation of other possible approaches of international law. The second criticism is against the  ideological neutrality in the study of our subject, showing the presence of a global north and south in academic production. For the preparation of this article, it will analyze contemporary literature both produced by Peruvian and foreign authors.